Collagenous gastroduodenitis with recurrent gastric ulcer in 12‐year‐old girl. Issue 4 (22nd May 2015) - Koide, Tatsuo; Mochizuki, Takahiro; Kawai, Naoki; Yashiro, Kenta; Inoue, Takeshi; Tsujimoto, Masahiko; Nishigaki, Toshinori
Abstract This report describes a rare case of collagenous gastroduodenitis found in a 12‐year‐old Japanese girl who had recurrent hematemesis. Gastrointestinal endoscopy showed many lotus leaf‐like lesions on the gastric mucosa surrounded by atrophic gastric mucosa in the antrum, with a cobblestone appearance and a scarred duodenal ulcer in the duodenal bulb. A biopsy of the gastric mucosa indicated subepithelial collagen band. The patient was treated with H2‐blockers for her symptoms for 4 years following the endoscopic findings. Follow‐up endoscopy showed the same appearance as before. The pathology, however, showed a more prominent subepithelial collagen deposition. To make the correct diagnosis, it is critical to know from which part the pathological biopsy specimens were taken because there were numerous collagen bands in the atrophic membrane. It is important to monitor the patient regularly for evaluation of the etiology, pathogenesis and prognosis of this rare disease.